The effects of 12 weeks of aerobic exercise on plasma Ghrelin, Insulin, GH, Cortisol Hormones concentration in male rats. - حسین عابد نظری; مرضیه مزرعه خطیری; سجاد احمدی زاد (Shahid Beheshti University, 2012)
Abjectivs: The purpose of this study was to investigate the effects of 12 weeks of treadmill running with modrate intensities on plasma Ghrelin and Glucose, Insulin, GH, Cottisol Hormon concentrations and relationship between this variable in male rat. Methods: Towenty Wistar male rats were used and randomly divided into two groups. control (n=9) and training group (n=11). The training group were given exercise on a motor-driven treadmil! (25m٫min. 60min. and 5 days٫weeks) for 12 weeks. Rats were sacrificed 48h after last training session. Plasma samples were collected, Ghrelin were meseared by ELISA and data were analyzed by T test, significance level was accepted at P<0.05 Results: The resalts indicate that plasma Ghrelin concentration in control(86.68+25.85pg٫1) and trained (59.72±5.41pg٫1) group that significantly decreased (t=6.9,P=0.0001) .Changes in weitgh (t=0.258.p=0.8) plasma glucose z(t=1.15.p=0.262) insulin (t=1.73.p=0.1). GH(1-1.75.pand cortisol (t=1.82.p=0.084) levels were not significant. Pearson correlation between the grelin and glucose, insulin, GH and cortisol concentrations assessed were not significant (P>0.05) Conclusion: it is concluded that long term treadmill exercise was effective on plasma ghrelin that this changes so changes of Insulin.GH and cortisol hormone can be related to time and intensity of training and time of fasting and rate of decrease of weight in exercise training.Also plasma ghrelin and GH concentration can be independent.